PERAN PERKUMPULAN REMAJA ISLAM DALAM MENUMBUHKAN KESADARAN BERAGAMA REMAJA KOTA (STUDI KASUS IRIC KELURAHAN PAMULANG BARAT KOTA TANGERANG SELATAN) - Bagas Zahran; Moh yasir Alimi (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to examine the role of Islamic youth organizations in fostering religious awareness among urban adolescents, using a case study of the Islamic Youth Community (IRIC) in Pamulang Barat Subdistrict, South Tangerang City. The research focuses on analyzing the contribution of religious activities, organizational development, and socio-religious programs in shaping adolescents’ religious awareness amid the complexities of urban life. This study employs a qualitative approach using a literature review method by examining books, scholarly journal articles, policy documents, and relevant previous studies related to Islamic youth and religious awareness. The findings indicate that Islamic youth organizations play a strategic role as platforms for religious development by instilling religious values, strengthening Islamic identity, and cultivating adolescents’ religious awareness through participatory and contextual approaches. Furthermore, these organizations function as positive socialization spaces that assist adolescents in coping with the challenges of modernization and urban environmental influences. In conclusion, Islamic youth organizations contribute significantly to the development of religious awareness among urban adolescents. Therefore, this study recommends sustained support from local governments and religious institutions to strengthen Islamic youth development programs.